2009
DOI: 10.1007/s11244-009-9204-6
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Highly Active Alumina-Pillared Clay Montmorillonite-Supported Platinum Catalyst for Hydrodesulfurization

Abstract: Effect of Pt precursor and pretreatment on hydrodesulfurization (HDS) activity of Pt/Al-PILM catalyst was examined to prepare highly active Pt-supported HDS catalyst. The order of HDS activities of Pt/aluminapillared clay montmorillonite (Al-PILM) catalysts prepared by various Pt precursors was Pt (C 5 6 . This order was in accordance with that of Pt dispersion. Thus, high Pt dispersion is essential factor to prepare highly active Pt/Al-PILM catalyst for HDS reaction. On the other hand, the effect of pretrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Recently, we reported that noble metal (NM), especially Pt, catalysts showed high and stable HDS activities 47) 53) . We proposed two reaction mechanisms for the HDS reaction: the monofunctional route occurring on Pt particles, and the bifunctional route occurring on Pt and Brønsted acid sites 47) 53) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we reported that noble metal (NM), especially Pt, catalysts showed high and stable HDS activities 47) 53) . We proposed two reaction mechanisms for the HDS reaction: the monofunctional route occurring on Pt particles, and the bifunctional route occurring on Pt and Brønsted acid sites 47) 53) .…”
Section: Introductionmentioning
confidence: 99%
“…We proposed two reaction mechanisms for the HDS reaction: the monofunctional route occurring on Pt particles, and the bifunctional route occurring on Pt and Brønsted acid sites 47) 53) . Therefore, noble metal phosphide catalyst, which has moderate hydrogenation activity, can be expected to show high HDS and HDN activities.…”
Section: Introductionmentioning
confidence: 99%
“…Especially, phosphat e salt s were widel y used as phosphorous source. Bussel et al [10] and Lee and Oyama et al [11] report ed t hat Ni 2 P cat alyst s support ed on silica (S iO 2 ) showed higher HDS act ivit y t han NiMo/ Al 2 O 3 cat alyst s. Thus, S iO 2 is a super ior support for preparat ion o f highly act ive phosphide cat alyst s. On t he ot her hand, we have report ed t hat noble met al (NM), especially plat inum (Pt ), support ed on zeo lit es [22 -24] and relat ed mat er ials, such as mesoporous silicat es [25 -27] and clays [24,28], showed high and st able act ivit y in HDS o f t hiophene. Thus, it is expect ed t hat noble met a l phosphides (NM X P Y ) show high cat alyt ic act ivit ies for HDS react ion, but HDS act ivit ies o f NM X P Y have not been report ed.…”
Section: Introductionmentioning
confidence: 99%
“…C−S activation of thiophene has been proposed to be a key step in the HDS process. Group 10 metal complexes were proved to be feasible catalysts in the HDS process recently, , and the model studies generally involved active zero-oxidation-state metal species prior to C−S cleavage, in which thiophene was coordinating in a η 2 -fashion, as suggested by recent DFT calculations. , A platinum(II) complex of η 2 -thiophene was also proposed as an intermediate in a C−S activation reaction, in which a cationic Pt(II) hydride complex was used as a starting material . Attempts to activate the C−S bond directly from 2 and 2′ and to force 2′ to undergo reductive elimination to form a platinum(0) species for C−S activation were unsuccessful, which prompted us to explore other platinum starting materials for C−S activation.…”
Section: Resultsmentioning
confidence: 99%